A robust and flexible bulk superhydrophobic material from silicone rubber/silica gel prepared by thiol–ene photopolymerization. Issue 12 (28th February 2019) - Li, Yongsheng; Ren, Meng; Lv, Pengfei; Liu, Yinzhi; Shao, Hong; Wang, Cong; Tang, Changyu; Zhou, Yuanlin; Shuai, Maobing
Abstract : A durable bulk superhydrophobic film based on silicone rubber/silica was prepared by UV curing followed by solvent evaporation. Abstract : Although bulk superhydrophobic materials are considered as promising candidates because of their durable anti-wetting properties, they still face some challenges such as complicated fabrication processes and inherent brittleness. In the present study, we prepared a robust and flexible bulk superhydrophobic film by a facile "UV curing + solvent evaporation" method. Using this method, a cross-linked organic gel is generated by rapid thiol–ene photopolymerization (within 60 s) of a polydimethylsiloxane (PDMS)/hydrophobic silica/cyclohexane suspension and is further transformed into a superhydrophobic porous film after solvent evaporation. With the optimized solvent/polymer mass ratio (15 : 1), the superhydrophobic PDMS/silica film shows high stretchability (∼68%) and solid mechanical strength because of the appropriate cross-linking degree and low porosity of the polymer skeleton. The silica particles and porous structure cooperatively form self-similar and hierarchical structures across the film bulk, which can be repetitively exposed to the surface by abrasion to maintain durable superhydrophobicity. Consequently, the robustness and regenerative characteristics of the hierarchical structure enable the film to maintain durable superhydrophobicity while facing various mechanical damages such as 1000 cycles of stretching–releasing and 500 abrasion cycles. Taking advantage of the regenerative characteristics, the damaged superhydrophobic film surface is rapidly recovered by sanding treatment without the use of healing agents.